Tropoxine in the effective dose does not affect on activity of CYP2С9 and CYP1А2 isoforms of cytochrome P450 in rats - V. P. Zherdev; G. B. Kolyvanov; A. A. Litvin; O. G. Grybakina; P. O. Bochkov; R. V. Shevchenko (LLC "Publisher OKI", 2017)
Effects of tropoxine on activity of isoforms CYP2С9 and CYP2С9 of cytochrome P450 using marker drugs losartane and caffeine were studied. Tropoxine in the effective dose (30 mg/kg) after 4-days intraperitoneal administration (3 times per day) in rats did not produce changes of CYP2C9 and CYP1A2 isoforms actitvity. Study of duration of tropoxine administration on the CYP2C9 acivity changing was shown that 3 and 4 days administration of the drug did not affect neither inhibiting nor inducing effect of CYP2C9 isoform.